The Values of Maqāṣid al-Sharī‘ah in the Implementation of Inclusive Education - Hasan Syahrizal; Fajrina Dhia Salsabila; Ainul Mardhiah (DZURRIYAT : Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Educational justice continues to face challenges when access and participation of children with special needs are not fully accommodated within formal education systems, requiring inclusive education to be grounded in a stronger philosophical and ethical foundation beyond administrative policy. This study aims to analyze the values of Maqāṣid al-Sharī‘ah in the implementation of inclusive education and to affirm their relevance as a normative basis for constructing a just educational system. The research employs a qualitative library research approach using normative and conceptual analysis of Maqāṣid al-Sharī‘ah literature and inclusive education policies. The findings indicate that inclusive education holds theological legitimacy within the framework of hifẓ al-‘aql through equitable intellectual development, hifẓ al-nafs and hifẓ al-nasl through the protection of dignity and generational continuity, and maslahah ‘āmmah through the strengthening of collective social welfare. The study implies that integrating Maqāṣid al-Sharī‘ah values into inclusive education policies and practices can reinforce a humane, just, and welfare-oriented Islamic educational system